The influence of cash conversion cycle, capital structure, and liquidity on profitability with firm size as moderation - Clarissa Fransisca; Ahmad Shalahuddin; Wendy Wendy; Giriati Giriati; Hasanudin Hasanudin (International Journal of Applied Finance and Business Studies, 2023)
This research analyses variables that influence profitability and corporate size as moderation. Three factors must be analyzed: cash conversion cycle, capital structure, and liquidity. This research examines how profitability is influenced by the cash conversion cycle, capital structure, and liquidity to profitability on major trading subsector firms publicly traded on the Indonesian Stock Exchange. Using the help of spss, this quantitative survey tested 100 panel data observations on the Indonesian Stock Exchange (BEI). According to the analysis, profitability is negatively impacted by cash conversion cycles and capital structures but positively affected by liquidity. Additional research indicates that company size amplifies the impact of the cash conversion cycle and capital structure on profitability but doesn't moderate the effect of liquidity on profitability. This suggests the role of corporate size as moderation